ANALISIS VARIASI WAKTU FERMENTASI TEH SARI ALANG-ALANG (Imperata cylindrica) TERHADAP KUALITAS PRODUK DAN ORGANOLEPTIK - Afrilia Sandra Ramadani; Pratiwi Jati Palupi (AGROINTEK, 2021)
Diversification of processed products became very rare on the market. Therefore, the need for further processing to enhanced added value to this crops. One product that hasn’t been developed yet is fermented tea blady grass extract. Commonly fermented beverages is made from fruits, however to developed the variety of functional food an the abundant of raw ingredient, then blady grass is choosen. The research purpose is to know the effect different fermentation time toward organoleptic analysis of cogon grass. Processing divided into three parts. The first step is fermentation of cogon grass, processing product syrup, and tea cogon grass fermentation drink. The result of this research shows that fermentation time while effect toward pH and anti oxidant activity. Whereas the sugar reduxtion not really affect. The best treatment of cogon grass fermentation gain 6 days of fermentation